The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.4314/ahs.v21i2.52
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and uptake of the UpToDate clinical decision support tool at the Makerere University College of Health Sciences (MakCHS), Uganda

Abstract: Background: The use of point-of-care, evidence-based tools is becoming increasingly popular. They can provide easy-to- use, high-quality information which is regularly updated and has been shown to improve clinical outcomes. Integrating such tools into clinical practice is an important component of improving the quality of health care. However, because such tools are rarely used in resource-limited settings, there is limited research on uptake especially among medical students. Objective: This paper expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…UpToDate® is a well-known medical knowledge source for physicians that is used in daily clinical practice in worldwide and our hospital [10]. Studies reported its effectiveness on health care quality, decreasing diagnostic error and mortality, association with shorter length of hospital stay, and lower complication rate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…UpToDate® is a well-known medical knowledge source for physicians that is used in daily clinical practice in worldwide and our hospital [10]. Studies reported its effectiveness on health care quality, decreasing diagnostic error and mortality, association with shorter length of hospital stay, and lower complication rate [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The remaining papers are on diverse issues such as availability of low vision services in Ghana; 50 utilization and uptake of the UpToDate clinical decision support tool51 at Makerere University in Uganda 51 ; hearing healthcare gaps in a semi-urban community in Nigeria 52 . A paper on ‘upper gastrointestinal endoscopy findings in Uganda 53 ; together with one on nutrition education on BMI-for-age in Ghanaian school-aged children 54 ; and factors contributing to obesity and overweigh in Morocco 55 give a glimpse on some aspects of nutrition in the continent.…”
mentioning
confidence: 99%